Evaluasi Penanganan Pascapanen dan Mutu Fisik Dalam Rantai Pasok Wortel di Kecamatan Tomohon Timur - Gregoria S. S. Djarkasi; Shanya E. Marie; Lana E. Lalujan; Maria F. Sumual (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
Carrot production in Tomohon City has exhibited a significant downward trend, with declines of 6.9% (2021–2022) and 14.6% (2022–2023), indicating critical constraints within the production systems and postharvest management. This study aims to evaluate postharvest handling procedures, map the supply chain, and identify critical points of physical quality degradation for carrots in East Tomohon District. A descriptive qualitative method was employed, involving a survey of 25 farmers and 15 in-chain actors, in-depth interviews, and field observations. The results indicate that most farmers (64%) and in-chain respondents (93%) have implemented basic postharvest handling, although methods remain largely market-driven. A key finding identifies that the critical point for physical damage occurs during the pre-harvest and harvesting stages (reaching 33%–50% due to agroclimatic factors), while the risk of damage during transportation is minimal. Furthermore, there is a notable power asymmetry, with 68% of quality grading being subjectively controlled by buyers. Although traditional markets dominate the local landscape, Tomohon carrots have established a regional reach, supplying markets in Kalimantan, Maluku, and Papua. This study recommends the standardization of harvesting techniques and the strengthening of farmer institutions to mitigate food loss and enhance the bargaining position of producers within the regional supply chain.